Irish Presbyterians and the shaping of western Pennsylvania, 1770-1830 - Gilmore, Peter E. (University of Pittsburgh Press, 2018)
"Irish Presbyterians and the Shaping of Western Pennsylvania, 1770-1830 is a historical study examining the religious culture of Irish immigrants in the early years of America. Despite fractious relations among competing sects, many immigrants shared a vision of a renewed Ireland in which their versions of Presbyterianism could flourish free from the domination of landlords and established church. In the process, they created the institutional foundations for western Pennsylvanian Presbyterian churches. Rural Presbyterian Irish church elders emphasized community and ethnoreligious group solidarity in supervising congregants' morality. Improved transportation and the greater reach of the market eliminated near-subsistence local economies and hastened the demise of religious traditions brought from Ireland. Gilmore contends that ritual and daily religious practice, as understood and carried out by migrant generations, were abandoned or altered by American-born generations in the context of major economic change"--